Mesoporous SiO2-TiO2 nanocomposite for pH sensing - Islam, Shumaila (Elsevier, 2015)
Abstract Thermally stable mesoporous silica-titania nanocomposite matrix was obtained via sol-gel method. The samples prior and after heat treatment were characterized by analytical instrumental techniques like Field Emission Scanning Electron Microscope (FE-SEM), Energy Dispersive X-ray Spectroscopy (EDX), Atomic Force Microscopy (AFM), X-ray Diffraction (XRD), Thermal Gravimetric Analysis (TGA), surface area, porosity measurements and UV-Vis Spectroscopy. The FE-SEM and AFM micrographs suggest that the indicator molecules are homogeneously diffused into matrix pores of the silica-titania network. The matrix exhibits regular morphology with large pores without any cracks. Energy Dispersive X-ray Spectroscopy (EDX) analysis verified the stoichiometric formation of encapsulated silica-titania nanocomposite matrix whereas calculated average crystallite size 3.82 nm was obtained by XRD. N2 adsorption isotherms explain the mesoporous nature of the silica-titania nanocomposite matrix with high surface area value of 401 m2/g with a pore size of 3.3 nm and pore volume of 0.33 cm3/g. UV-vis spectroscopic determinations revealed that the prepared nanomatrix shows good sensitivity between pH range of 3-5 for acidic medium within 6.9 s and pH 12 for basic medium within 1.03 s; it is indicative that pH sensor is more responsive toward strong basis. It can be deduced that the sensing species are probably better encapsulated in the matrix and show faster response time. The fabricated pH sensor was found to have a six months age stability and high reproducibility in terms of absorption and color stability with response time. A reversible response over a range of pH values between 3 and 12 were obtained. The encapsulated pH indicator silica-titania nanocomposite matrix after 2 h heating at 150°C shows a great potential to be used as pH sensor with good material stability, reproducibility/repeatability, reversibility, fast response and long life time behavior.